The Relationship Between Lower Extremity Sports Injuries and Stress Levels Among SSB Bina Muda Players In Sukatani District, Bekasi Regency - Nawasul, Faid; Saryono, Saryono; Gemael, Qorry Armen; Izzuddin, Deden Akbar; Aulia, Dany (UNIVERSITAS NEGERI MAKASSAR, 2025)
The Relationship Between Lower Extremity Sports Injuries and Stress Levels Among SSB Bina Muda Sukatani Players, Kabupaten Bekasi Sports injuries are a major factor affecting an athlete's physical and psychological condition. Lower extremity injuries are common among football players and can disrupt training sessions and matches. Stress is a physiological and psychological response to the pressure players face due to injuries. This study aims to examine the relationship between lower extremity sports injuries and stress levels among players at SSB Bina Muda Sukatani, Kabupaten Bekasi. This research employs a quantitative correlational design. The sample consists of 30 football players who have experienced lower extremity injuries. Data collection was conducted using the Functional Movement Screen (FMS) to measure injury levels and the Perceived Stress Scale (PSS) to assess players’ stress levels. Data analysis involved normality tests, linearity tests, Pearson correlation tests, and simple linear regression analysis using SPSS 26 software. The results indicate a significant relationship between lower extremity injuries and stress levels, with a correlation coefficient of 0.573, categorized as a moderate correlation. The more severe the injury, the higher the stress level experienced by the players. The primary cause of injuries was insufficient warm-up before training and matches. Severe injuries tend to increase psychological stress, whereas minor injuries have a lesser impact on players' mental well-being. Based on these findings, it is recommended that players and coaches focus on injury prevention training, including proper warm-up routines, muscle-strengthening exercises, and stress management programs to minimize the psychological effects of injuries.